Role of the dielectric constant of ferroelectric ceramic in enhancing the ionic conductivity of a polymer electrolyte composite - Singh P.K.; Chandra A. (My University, 2025)
The effect of dispersal of ferroelectric ceramic materials Ba0.70Sr0.30TiO3 (Tc ≈ 30°C) and Ba0.88Sr0.12TiO3 (Tc ≈ 90°C) on the ionic conductivity of an ion conducting polymer electrolyte (PEO:NH4I) is reported. The addition of 3 wt% of Ba1-xSrxTiO3 (x = 0.30 and 0.12) results in an increase in the conductivity by one to two orders of magnitude. Further, a study on the temperature dependence of conductivity of these composites shows that the conductivity enhancement 'peaks' as we approach the dielectric phase transition of the dispersed ferroelectric material where the ε changes rapidly from ∼2400 to 7500 (for x = 0.30) and from 1100 to 5500 (for x = 0.12). This establishes the role of dielectric constant of the dispersoid in enhancing the ionic conductivity of the polymeric composites.